Cooperative Learning sebagai solusi pembelajaran teknik dasar Bulutangkis - Rubiyatno Rubiyatno (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study is entitled "Cooperative Learning as a solution to learning basic badminton techniques" the purpose of this study is to apply cooperative learning methods in learning badminton. The form of research used in this study used Classroom Action Research with two cycles consisting of planning, implementation, observation, reflection, and conclusion. The subjects in this study were 34 students of SMP N 3 Pontianak City, namely 19 girls and 15 boys.The results of improving badminton basic technical skills were obtained by comparing the observation value with the initial test before the action known as "pre-cycle". Based on the results of observations that have been carried out, there is an increase in student scores in each cycle in the pre-cycle student completeness only reaches 8 students or 24% then a slight increase in the first cycle which is 15 students who are complete or 44% then seeing the results of cycle 1 it turns out that it still does not reach the specified target so the researcher continues to cycle 2 as for this second cycle there is a significant increase in the number of students who are complete reaching 27 students or 87.5%. Seeing this data, the target of 75% classical completeness has been achieved so it can be concluded that through cooperative learning methods can improve the learning of basic badminton techniques in class VIII students of State Junior High School 3 Pontianak.